Oral lichenoid drug reaction - Zain, R.B.; Nor, G.M. (1988)
This is a case report of an oral lichenoid drug reaction of the buccal sulci in a female diabetic patient who was on an anti-hypertensive drug, alpha-methyldopa (Aldomet) and an oral hypoglycaemic drug, chlorpropamide (Diabinese). The clinical features, histological findings and management are presented.